The Diversity of Wild Banana Species (Genus Musa) in Java - Sulistyaningsih, Lulut Dwi (UI Scholars Hub, 2016)
The diversity of wild banana species (genus Musa, listed in Flora of Java) has been revised. The present taxonomic study is based on morphological characteristics observed in the herbarium specimens deposited at the Herbarium Bogoriense (BO), living collections in the Bogor Botanical Garden, the Cibodas Botanical Garden, and during the explorations done at Mt. Salak, West Java. Eight species of Musa (Musa acuminata, M. balbisiana, M. coccinea, M. ornata, M. salaccensis, M. sanguinea, M. textilis and M. velutina) and seven infraspecific taxa of M. acuminata are recognized in Java, of which two infraspecific taxa are endemic. West Java is the center of distribution for the wild banana species in Java. Taxonomic descriptions including an identification key are presented.